The geographic decentralization of audit firms and audit quality - Beck, Matthew J.; Gunn, Joshua L.; Hallman, Nicholas (Journal of Accounting and Economics, 2019)
Audit firms are organized as collections of geographically decentralized offices. Decentralization allows for increased proximity between offices and clients, improving the efficiency of auditors' interactions with client personnel. Yet decentralization also decreases the proximity between offices within each firm, potentially impeding auditors’ interactions with each other. We show that decreased proximity between offices reduces inter-office audit quality “spillovers” and that this effect is driven primarily by reduced monitoring and knowledge sharing. Our findings expand the “within office” view of audit production by demonstrating the importance of interactions between offices and the role of geographic proximity in facilitating them.